The Environmental Fate of Natural and Synthetic Oestrogens; Comparison between Prediction Tools and Experimental Values - E. A., Aziz; W. A., Wan Omar; N. A., Zainordin (IACSIT Press, 2015)
The increasing demand for clean water leads to reuse practices such as the uses of sewage effluent in crops irrigation. However, the extent to which the effluent is safe to be used as irrigation water remains uncertain. Natural and synthetic oestrogens are ubiquitous in effluents and they are present in the final effluents for the vast majority of waste water treatment plants. Thus for this study, it was necessary to determine their sorption to soils in order to assess the possible human exposure from irrigation water. EPISUITE uses a prediction model whereby the inherent chemical and physical properties are used to determine the partition coefficients for each environmental compartment. However, this is a default model which can be made more accurate by experimentally measuring these partition coefficients. The Kow, Koc and Kd of these compounds were measured and computed to determine environmental fate. The experimental model was later compared to the default model. It can be concluded that by inputting the experimental values, the model changes remarkably and has given absolute values to the ambient conditions.